2017
DOI: 10.1038/sdata.2017.63
|View full text |Cite|
|
Sign up to set email alerts
|

A new, long-term daily satellite-based rainfall dataset for operational monitoring in Africa

Abstract: Rainfall information is essential for many applications in developing countries, and yet, continually updated information at fine temporal and spatial scales is lacking. In Africa, rainfall monitoring is particularly important given the close relationship between climate and livelihoods. To address this information gap, this paper describes two versions (v2.0 and v3.0) of the TAMSAT daily rainfall dataset based on high-resolution thermal-infrared observations, available from 1983 to the present. The datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
188
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(192 citation statements)
references
References 59 publications
4
188
0
Order By: Relevance
“…The works of Toté et al (2015) in Mozambique can be mentioned here as the first validation work we are aware of that reveals the potential applications of CHIRPS in Africa. Maidment et al (2017) have also validated the performance of satellite rainfall products (including CHIRPS V 2.0) in four countries in Africa (Mozambique, Nigeria, Uganda, and Zambia). In general, these few validation works have shown the promising skills of CHIRPS in Africa and its potentials for various working applications in the continent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The works of Toté et al (2015) in Mozambique can be mentioned here as the first validation work we are aware of that reveals the potential applications of CHIRPS in Africa. Maidment et al (2017) have also validated the performance of satellite rainfall products (including CHIRPS V 2.0) in four countries in Africa (Mozambique, Nigeria, Uganda, and Zambia). In general, these few validation works have shown the promising skills of CHIRPS in Africa and its potentials for various working applications in the continent.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of this analysis, both the TAMSAT and ARC 2 products have been validated as well. Also, this study has also been paid some courtesy to compare TAMSAT 2 and TAMSAT 3 products to assess the improvements made with the new version (TAMSAT 3, Maidment et al, 2017). The analyses used dekadal (10 days) and monthly time scale rainfall data both from the satellite products and rain 25 gauge observations.…”
Section: Introductionmentioning
confidence: 99%
“…The rainfall estimates are derived from Meteosat thermal infrared images calibrated against an extensive network of African rain gauges. When aggregated over time and space, TAMSAT has been shown to have good skill over much of Africa, in comparison to ground-based observations (Maidment et al, 2013(Maidment et al, , 2017. On daily time scales, occurrence is better represented than amount (Greatrex et al, 2014), with the magnitude of high intensity rainfall events not captured.…”
Section: Tamsat Rainfall Observationsmentioning
confidence: 99%
“…The difference between JULES model outputs when forced with these two distinct products will help us to understand the impact of improved precipitation forcing on our estimation of soil moisture. It has been shown that TAMSAT v3.0 has greatly reduced the dry bias present in TAMSAT v2.0 (Maidment et al, 2017) and has eliminated the spatial artefacts. Despite this there are still areas 5 where both products struggle, with coastal regions subject to large amounts of warm rain, and sharp topographic contrasts, being an example of this.…”
Section: Tamsat Rainfall Observationsmentioning
confidence: 99%
“…In this context, precipitation retrievals from a satellite provide an alternative solution to this problem by providing spatially distributed precipitation estimation over large areas. Various aspects of remotely-sensed rainfall have been explored and reported [16][17][18][19][20]. Among them, Tropical Rainfall Measuring Mission (TRMM) multisatellite precipitation analysis (TMPA) has been used, since the launch of TRMM in November 1997, to produce a range of quasi-global precipitation products.…”
Section: Introductionmentioning
confidence: 99%